A bimetallic ZIFs-triggered hierarchical carbon structure for stabilized silicon anode. (20th January 2022) - Niu, Xingxin; Wang, Chengdeng; Zhang, Wenyuan; Wang, Donghua; Shi, Haofeng; Yu, Lu; Wang, Chong; Xiong, Zhihao; Ji, Zhen; Gao, Yan; Yan, Xiaoqin
Highlights: An N-doped CNT-interspersed hierarchical carbon shell structure by Co-Zn bimetallic ZIFs-triggered surface polymerization of dopamine has been designed and successfully prepared for stabilized silicon anode (PDA@CoZn-NC@Si). PDA@CoZn-NC@Si electrodes deliver better cycle stability of 814 mAh/g at 0.5C with a capacity loss of −0.14% per cycle over 400 cycles and possess excellent rate capability. The solution-based chemical prelithiation method is used to compensate for irreversible loss of anode capacity, and the full cell exhibits an improved ICE (88.3%) and a higher energy density (419.8 Wh kg −1 ). Abstract: The application of silicon-based anode remains a serious challenge due to its intrinsic volumetric expansion effect and low conductivity. In our work, a novel CNT-interspersed hierarchical carbon shell structure (denoted as PDA@CoZn-NC@Si) is synthesized by wrapping Si uniformly in the bimetallic zeolite imidazolate frameworks (ZIFs) and then encapsulated with a dopamine-derived carbon shell. The PDA@CoZn-NC@Si anode delivers better cycle stability of 814 mAh/g at 0.5C for 400 cycles (only −0.14% capacity reduction per cycle) and possesses excellent rate capability, which benefits from the inner porous buffer spaces, interspersed CNT, and solid heterogeneous carbon shells. In addition, the full cell is assembled by pairing a solution-based chemically prelithiated PDA@CoZn-NC@Si anode with a Li(Ni1/3 Co1/3 Mn1/3 )O2 (NCM111) cathode, and it presents an improved initial coulombic efficiency (88.3%) and a high energy density (419.8 Wh/kg). This study provides effective guidance for optimizing the microstructure design and prelithium of Si-based anodes.